Evaluating science curriculum content standards according to the visual thinking skills of basic education stage pupils - Al-Khaddour, Abeer Ayman; Hamada, Walid Abdel Karim (Journal of Educational and Psychological Sciences, 2021)
The aim of the research is to define the degree to which visual thinking skills are achieved in the science curriculum among students of the basic education stage (grades two and six). To achieve the goal, the researcher used a list of visual thinking skills especially for the sixth grade textbook consisting of 30 criteria distributed on 7 axes (skills) A list of visual thinking skills for the second grade book, consisting of 34 criteria distributed into 7 axes (skills) for the sixth grade book, consisting of 30 criteria distributed into 7 axes (skills). The results of the research concluded that the skills are available in the second and sixth grades as follows: The visual discernment skill was of medium rank 1, visual proficiency 2 was also moderate, visual translation skill 3 moderate, visual contemplation 4 moderate, visual observation skill 5 weak, visual imagination 6 poor, and visual closure 7 poor. In light of the search results, we recommend the following: 1- Attention by the curriculum authors to the skills of visual thinking by conducting full-fledged teaching courses for these skills. 2- Educating science teachers about visual thinking skills, and holding training courses in employing visual thinking skills in science classes, in a way that serves the achievement of national standards for education in Syria.